In Vitro Effectiveness of Beauveria bassiana as a Control Agent against Invasive Fall Armyworm (Spodoptera frugiperda) Larvae - Purwanti, Eny Wahyuning; Mulyasari, Julisa Ginti; Budianto, Budianto (Universitas Gadjah Mada, 2022)
Fall armyworm or Spodoptera frugiperda is one of the main pests of corn. It can caused up to 28.08% yield loss. Pest control efforts with broad-spectrum insecticides can cause negative impacts that disrupt ecosystems, non-target biotic factors and the surrounding environment. Beauveria bassiana is an alternative biological control agent that is target-specific. This study was conducted to determine toxic and antifeedant activities of B. bassiana application on third to fifth-instar S. frugiperda larvae. B. bassiana isolates were propagated using corn flakes media and resulted in colonies with conidia density of 1.1×108conidia.g-1. This study used a completely randomized design with 5 treatments and 5 replications. Treatments consisted of P1 namely B. bassiana propagation with a concentration of 60 g.L-1, P2 = 70 g.L-1, and P3 = 80 g.L-1. P0 was a negative control (untreated with B. bassiana) and P4 was a positive control (diazinon with concentrations of 2 ml.L-1). The variables observed were mortality and weight of the leftover feed. The results showed that the formulation of B. bassiana with concentrations of 80 g.L-1 was able to infect armyworms with a mortality percentage of 53.5% which was statistically similar as the effect of chemical insecticides. In addition, inhibition of feeding activity due to treatment could prevent leaf damage up to 68.21%.